Similarity Among 10 Cayenne Pepper (Capsicum frutescens L.) Mutant Accessions Resulted from Gamma-Ray Irradiation - Asya Zhafira Khairunissa; Makhziah Makhziah; Djarwatiningsih Poengky Soedjarwo (The University of Lampung, 2025)
Cayenne pepper (Capsicum frutescens L.) is a horticultural crop which production is not comparable to the level of public consumption. Chili plants induced by gamma irradiation experienced character changes, which caused the population of mutant accessions to have a diversity of characters. The similarity test of mutant accessions was carried out to determine the relationship distance between accessions. The research was carried out at the Faculty of Agriculture, UPN